Uji Bioaktivator MOL dan EM4 dalam Fermentasi Pupuk Kandang Sapi terhadap Pertumbuhan Awal Tanaman Jahe (Zingiber officinale): Evaluation of MOL and EM4 Bioactivators in the Fermentation of Cow Manure on the Early Growth of Ginger (Zingiber officinale) - Surya Ari Widya; Medita Johana Pakula Bafiqi; Dharma Setiawan; Hakkul Bahiz Mahdani; Erfan Andrianto Aritonang (Agrocentrum, 2026)
This study aimed to determine the effect of bioactivators, namely Local Microorganisms (MOL) and EM4, in the fermentation of cow manure on the early growth of ginger (Zingiber officinale). The research was conducted from July to September 2024 using a non-factorial Completely Randomized Design (CRD) with three treatments: cow manure without bioactivator (P1), cow manure fermented with MOL (P2), and cow manure fermented with EM4 (P3), each replicated three times. Observed parameters included plant height, number of leaves, and number of shoots. Data were analyzed using ANOVA followed by LSD test at 5%. The results showed that bioactivator application significantly affected plant height, with EM4 treatment producing the highest growth. Meanwhile, the number of leaves and shoots did not show significant differences, although descriptively EM4 tended to give higher values. These findings indicate that the use of bioactivators, particularly EM4, can enhance early growth of ginger, although its effect is not yet optimal across all parameters.